2014
DOI: 10.1016/j.jalz.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Carriers of a common variant in the dopamine transporter gene have greater dementia risk, cognitive decline, and faster ventricular expansion

Abstract: Background Genetic variants in DAT1, the gene encoding the dopamine transporter protein (DAT), have been implicated in many brain disorders. In a recent case-control study of Alzheimer’s disease (AD), a regulatory polymorphism in DAT1 showed a significant association with the clinical stages of dementia. Methods We tested whether this variant was associated with increased AD risk, and with measures of cognitive decline and longitudinal ventricular expansion, in a large sample of elderly participants with gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Dopamine transporter protein, encoded by the DAT1 gene, regulates neurotransmission by modulating dopamine receptors. The minor C allele of rs6347 in DAT1 was associated with poorer cognitive performance, greater ventricular expansion, and greater dementia risk, independent of APOE genotype [194]. Although the mechanism of action of this polymorphism is unknown, dopamine neurotransmission may be a useful target for anti-dementia drugs.…”
Section: Studies Of Genetic Associationsmentioning
confidence: 99%
“…Dopamine transporter protein, encoded by the DAT1 gene, regulates neurotransmission by modulating dopamine receptors. The minor C allele of rs6347 in DAT1 was associated with poorer cognitive performance, greater ventricular expansion, and greater dementia risk, independent of APOE genotype [194]. Although the mechanism of action of this polymorphism is unknown, dopamine neurotransmission may be a useful target for anti-dementia drugs.…”
Section: Studies Of Genetic Associationsmentioning
confidence: 99%
“…In the other study [39], they identified several SNPs that modify the relationships between amyloid-beta (Aβ) or tau positivity and neurodegeneration. Roussotte et al performed a series of ADNI MRI-based genetic studies [4043] and identified a common variant in the DAT1 (dopamine transporter; also known as SLC6A3, solute carrier family 6 (neurotransmitter transporter), member 3) gene associated with faster ventricular expansion [40], combined effects of LOAD risk variants in the CLU (clusterin) and APOE genes on ventricular expansion [41], a common variant in the OPRD1 (opioid receptor, delta 1) gene associated with smaller regional brain volumes [42], and a variant in the RASGRF2 (Ras protein-specific guanine nucleotide-releasing factor 2) gene associated with larger cortical volume but faster longitudinal ventricular expansion [43]. Luis et al [44] performed an MRI-based genetic study on the TREM2 (triggering receptor expressed on myeloid cells 2) AD risk variant (rs75932628), which included ADNI and a Spanish cohort, and identified an association between the TREM2 variant and frontobasal grey matter loss.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have related genes to cognition following the discovery of a primary association with a non-cognitive phenotype, including ASTND2 (astrotactin 2) and GRIN2B (glutamate receptor, ionotropic, N-methyl D-aspartate 2B) with hippocampal and temporal lobe atrophy on MRI [83, 84], PSEN1 (presenilin 1) with CSF amyloid levels [85], and DAT1 with AD case-control status [40]. Alternatively, pathway analysis has been used to elucidate collective effects of multiple genes on memory [86], executive functioning [87], and depressive symptoms [88].…”
Section: Resultsmentioning
confidence: 99%
“…In physiological conditions, the targeted genetic variants can perform a direct effect on phenotypes, but also mediate an influence through the interaction with other genes, or via a downstream functional change. Future studies should ascertain whether these SNPs are authentic regulatory variants (and if so, how it may impact protein expression) or if they are simply flagging a region comprised of another functional variant (Roussotte et al, 2015).…”
Section: Discussionmentioning
confidence: 99%